ORAL Literature As A Tourism Communication Strategy In Singkawang City - Ayu Annisa; Chairil Effendy; Antonius Totok Priyadi; Khairullah (INJECT (Interdisciplinary Journal of Communication), 2026)
This study examines oral literature as a form of cultural communication that underlies literary tourism in Singkawang City, framing the inquiry within the field of interdisciplinary communication science. Using a descriptive qualitative method, data were gathered through observation and interviews with storytellers, destination managers, and local government officials, supplemented by recording, transcription, and editing techniques. The findings reveal six folktales: Batu Belimbing, Gunung Poteng, Sibohe Waterfall, Bagak Sahwa Village, Tjhia Family House, and Batu Burung Beach, all classified as legends that function as narrative communication foundations for their respective tourist sites. Analysis of the communication context surrounding these narratives shows that intergenerational oral transmission is declining, with storytellers aged 29 to 73, and that the communicative occasions for these stories are shifting from family-based communication to more institutionalized forms such as theatrical performances or tourist-oriented communication encounters. The messages embedded in these oral narratives convey ecological, moral, and cultural values that function as communicative guidance for tourism management. Infrastructural assessment of the six destinations reveals significant disparities in how effectively each site communicates its narrative heritage to visitors: Batu Belimbing and Tjhia Family House are comparatively well-managed, while Gunung Poteng and Sibohe Waterfall remain critically underdeveloped. The study argues that positioning oral literature as a communication strategy within literary tourism offers a culturally grounded and sustainable path for heritage communication and tourism development in multiethnic border cities, contributing to interdisciplinary dialogue between communication science and cultural tourism studies.